Synthesis and Characterization of Tridentate Schiff Base Derivative of Indenyl Lanthanoid Chloride Tetrahydrofuranate Complexes for Catalytic Applications - Yousaf, Muhammad; Fawad Zahoor, Ameer; Anjum, Anbreen; Hussain Bokhari, Tanveer; Ghulam Ali, Kulsoom; Purveen, Bushra; Naheed, Shazia; Jabbar, Abdul; Badaruddin Ahmad, Hafiz (Asian Journal of Chemistry, 2012)
Four kinds of novel lanthanocene complexes were synthesized in reasonable yield by the reaction of equimolar quantity of sodium salt of tridentate Schiff base [N-(2-methoxyphenyl)salicylideneimine] with indenyl lanthanoid dichloride tetrahydrofuranate in tetrahydrofuran. All the complexes after purification were characterized by MS and EA, respectively. These complexes isomerized successfully the 1,5-hexadiene into a mixture of products such as 1,4-hexadiene, 2,4-hexadiene,1,3-hexadiene, methylenecyclopentane and methylcyclopentene. Similarly they also proved effective for the polymerization of methylmethacrylate (MMA), 56.45 % yield and high molecular weight (355 × 103).